THE EFFECT OF TANSFORMATIONAL, TRANSACTIONAL, AUTHENTIC AND AUTHORITARIAN LEADERSHIP STYLE TOWARD LECTURE PERFORMANCE OF PRIVATE UNIVERSITY IN TANGERANG - Purwanto, Agus; Wijayanti, Laksmi Mayesti; Hyun, Choi Chi; Asbari, Masduki (Dinasti International Journal of Digital Business Management, 2019)
The aim of this study is to analyze the effect of transformational, transactional, authentic and authoritarian leadership styles toward lecture performance in some private university in Tangerang. The study population are lecture of private university as many as 120 lectures from 14 of private university and data collection methods by giving an electronics questionnaire to the lectures of private university in Tangerang. The data analysis tool of this study uses SEM (Structural Equation Model) the LISREL program version 8.70. The results show that the transformational, transactional and authorian leadership style have positive and significant affected to lecture performance. Transformational leadership and authentic leadership has no significant effect to lecture performance.